How Do People Analyze Data for Visual Identity Design Projects? A Systematic Literature Review in Indonesian Projects - Hananto, Brian Alvin (Universitas Pelita Harapan, 2024)
Over the past five years, numerous visual identity design projects have been carried out in Indonesia, reflecting the growing importance of this field. This systematic literature review aims to identify the data analysis methods commonly used in these design processes. Using Publish or Perish and Google Scholar databases, the review examined articles published in the past five years with the title